2011
DOI: 10.1245/s10434-011-2095-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Primary Melanoma Thickness and Microscopic Tumor Burden in Sentinel Lymph Nodes on Melanoma Patient Survival

Abstract: PMT and MMS were independently prognostic of PFS and OS in melanoma patients. Patients with negative CLND had significantly better PFS and OS than those with positive CLND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
1
13
0
2
Order By: Relevance
“…When stratified by thickness, the estimated 5-year progression-free survival rates were 95% for patients with maximum metastatic size <1.6 mm, 70% between 1.6 and 4.5 mm, and 45% >4.5 mm; the overall survival were 82%, 52%, and 5%. Both primary melanoma thickness and maximum metastatic size were independently prognostic of progression-free survival and overall survival in melanoma patients (Baehner et al, 2011). Other studies have also demonstrated that the incidence of SLN metastases correlates directly with increasing tumor thickness (Gershenwald et al, 1998; as well as other factors including ulceration, lymphatic invasion, mitotic rate, Clark level, and anatomic site .…”
Section: Biology and Clinical Impact Of Micrometastasis In Sln(s)mentioning
confidence: 93%
See 1 more Smart Citation
“…When stratified by thickness, the estimated 5-year progression-free survival rates were 95% for patients with maximum metastatic size <1.6 mm, 70% between 1.6 and 4.5 mm, and 45% >4.5 mm; the overall survival were 82%, 52%, and 5%. Both primary melanoma thickness and maximum metastatic size were independently prognostic of progression-free survival and overall survival in melanoma patients (Baehner et al, 2011). Other studies have also demonstrated that the incidence of SLN metastases correlates directly with increasing tumor thickness (Gershenwald et al, 1998; as well as other factors including ulceration, lymphatic invasion, mitotic rate, Clark level, and anatomic site .…”
Section: Biology and Clinical Impact Of Micrometastasis In Sln(s)mentioning
confidence: 93%
“…Both T4 and SLN tumor burden were the most important factors for overall survival. Similarly, 63 melanoma patients with positive SLNs from the UCSF melanoma SLN database with a median follow-up of 8 years were analyzed (Baehner et al, 2011). SLN micrometastasis was recorded for size, number of foci and anatomic location by H&E. Fourteen of 63 patients had positive non-SLNs.…”
Section: Biology and Clinical Impact Of Micrometastasis In Sln(s)mentioning
confidence: 99%
“…Recently, we have completed a study to correlate the extent of microscopic tumor burden in melanoma SLNs with PFS and OS [123]. Further, we have explored the independent contributions of extent of SLN tumor burden and primary melanoma thickness (PMT) with respect to PFS and OS.…”
Section: Impact Of Melanoma Sln Micrometastasis On Clinical Outcomesmentioning
confidence: 99%
“…Our recent work and others on melanoma SLN micrometastasis shows that different amount of tumor burden in SLN is correlated with various clinical outcomes of patients with less tumor burden being associated with more favorable outcome. Further, we have found that both primary melanoma thickness and SLN tumor burden progressively affect the disease-free survival and overall in melanoma patients ((19)). Thus, SLN tumor burden further supports the spectrum theory of cancer progression ((5)).…”
Section: As Biomarkers Of Metastasismentioning
confidence: 99%